2020
DOI: 10.15557/pipk.2020.0014
|View full text |Cite
|
Sign up to set email alerts
|

Differential prevalence of depressive and narcissistic traits in competing and non-competing bodybuilders in relation to muscle dysmorphia levels

Abstract: Background: Muscle dysmorphia is considered a subtype of body dysmorphic disorder with a high prevalence in bodybuilders. Observational and experimental data suggest a differential prevalence for depressive and narcissistic-like traits between people involved in competing or non-competing bodybuilding activity. Methods: Here we assessed symptoms related to muscle dysmorphia (Muscle Dysmorphic Disorder Inventory, MDDI), depression (Back Depression Inventory, BDI), and narcissism (Narcissistic Personality Invent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Within the framework of this finding, it can be thought that this mindset may be a predictive factor in the development of the narcissistic characteristics of individuals (Tazegül & Güven, 2015). Dettore, Fabris, Santarnecchi (2020) suggested that potential interaction between MD symptoms and narcissism has a stronger association between narcissistic traits and the development of more severe MD conditions in competing bodybuilders. Similarly, in this study, NPI scores of bodybuilding individuals were found to be significantly higher than sedentary individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Within the framework of this finding, it can be thought that this mindset may be a predictive factor in the development of the narcissistic characteristics of individuals (Tazegül & Güven, 2015). Dettore, Fabris, Santarnecchi (2020) suggested that potential interaction between MD symptoms and narcissism has a stronger association between narcissistic traits and the development of more severe MD conditions in competing bodybuilders. Similarly, in this study, NPI scores of bodybuilding individuals were found to be significantly higher than sedentary individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, international studies have been developed on excess muscle mass as a condition, megarexia as opposed to excessive weight loss anorexia, an important contribution being made by the study of italian researchers [16] muscle dysmorphia is considered a subtype of body dysmorphic disorder with a high prevalence at bodybuilders. Symptoms related to muscle dysmorphia (Inventory of Muscle Dysmorphic Disorders, MDDI), depression (Inventory of Back Depression, BDI) and narcissism (Inventory of Narcissistic Personality, NPI) (among other dimensions) were evaluated in 260 subjects, competing and non-competing bodybuilders.…”
Section: Introductionmentioning
confidence: 99%